Proceedings of the Eleventh ACM International Conference on Multimedia 2003
DOI: 10.1145/957013.957143
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia content processing through cross-modal association

Abstract: Multimodal information processing has received considerable attention in recent years. The focus of existing research in this area has been predominantly on the use of fusion technology. In this paper, we suggest that cross-modal association can provide a new set of powerful solutions in this area. We investigate different cross-modal association methods using the linear correlation model. We also introduce a novel method for cross-modal association called Crossmodal Factor Analysis (CFA). Our earlier work on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
125
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(128 citation statements)
references
References 9 publications
0
125
0
3
Order By: Relevance
“…There are 10 state-of-the-art compared methods in the experiment: CCA [2], KCCA (with Gaussian kernel and polynomial kernel) [3], CFA [4], JRL [5], LGCFL [6], Multimodal DBN [22], Bimodal AE [9], Corr-AE [10], CMDN [11], and Deep-SM [12]. CCA, KCCA, CFA, JRL, LGCFL are traditional methods without deep learning, and Multimodal DBN, Bimodal AE, Corr-AE, CMDN, and Deep-SM are deep learning methods.…”
Section: Compared Methods and Evaluation Settingsmentioning
confidence: 99%
“…There are 10 state-of-the-art compared methods in the experiment: CCA [2], KCCA (with Gaussian kernel and polynomial kernel) [3], CFA [4], JRL [5], LGCFL [6], Multimodal DBN [22], Bimodal AE [9], Corr-AE [10], CMDN [11], and Deep-SM [12]. CCA, KCCA, CFA, JRL, LGCFL are traditional methods without deep learning, and Multimodal DBN, Bimodal AE, Corr-AE, CMDN, and Deep-SM are deep learning methods.…”
Section: Compared Methods and Evaluation Settingsmentioning
confidence: 99%
“…It also utilizes relevence feedback to improve the results. Similarly, in [6], a method for crossmodal association called Cross-modal Factor Analysis (CFA) is introduced. The method achieves significant dimensionality reduction, while it effectively identifies the correlations between two different modalities.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Snoek et al proposed concept-based video retrieval method [7] and Yan et al studied a multimodal retrieval approach including text and image for broadcast new video [8]. D. Li et al [9] suggested cross-modal association based factor analysis method as alternatives to Latent Semantic Indexing (LSI) and Canonical Correlation Analysis (CCA). Ferecatu et al showed that the joint use of visual features and concept-based features with relevance feedback scheme improves the quality of the cross-modal image retrieval [10].…”
Section: Related Workmentioning
confidence: 99%